Synthesis and shape memory behavior of hyperbranched polyimides from thiol-ene click reaction - Y. F. Lu; Y. M. Wang; X. D. Chen; M. H. Miao; D. H. Zhang (eXPRESS Polymer Letters)
Shape memory polymers (SMPs) with novel functions have received increasing attention, but hyperbranched polyimide (HBPI)-based SMPs have rarely been reported. Herein, we have synthesized a series of thiol-ended hyperbranched polyimides (BTMP-n, n = 6, 9, 11) with various molecular weights using a thiol-ene click reaction, and BTMP-n was used as a crosslinking agent with 1-methacryl-allyl ethoxyethyl-diphenyl phosphate (AGDP) to prepare SMPs (BTMP-n-AGDP). The chemical structure and molecular weight of BTMP-n were characterized by Fourier transform infrared (FTIR) spectroscopy, proton nuclear magnetic resonance (1H NMR) spectroscopy, and matrix-assisted laser desorption ionization timeof-flight (MALDI-TOF) mass spectroscopy. The shape fixity ratios and shape recovery ratios of BTMP-n-AGDP were over 99% and over 90%, respectively, indicating excellent shape memory properties. The excellent cycling stability of BTMP-n-AGDP was also demonstrated using the shape recovery sharpness over consecutive cycles. A rapid transition between the temporary shape and permanent shape of the BTMP-n-AGDP was discovered using the large shape recovery sharpness and a cramped strain recovery transition breadth. The results provide a new method for obtaining high-performance SMPs.